Effect of Abiotic Factors on the Population of Calopepla leayana Latr. (Coleoptera: Chrysomelidae) on Gmelina arborea (Roxb.) (Verbenaceae) - Kumar, N. Senthil; Sarma, Saurabh; Barthakur, Nizara D. (Indian Forester, 2010)
The population dynamics of Calopepla leayana Late, a serious (monophagous) defoliator of the commercially important timber species, Gmelina arborea (Roxb.), in Assam, India, was studied in terms of the fluctuation in their abundance in relation to temporal changes in the abiotic factors. Adults as well as larvae were recorded from March to November after which they undergo a brief period of diapause during winter. The population was observed maximum in the month of August when the interacting factors such as temperature and precipitation were high. Statistical analysis of the population data using forward stepwise regression and principal component analysis revealed temperature to be the principal component influencing the population.